“National Intervention” in International Commercial Arbitration - Esplugues, Carlos (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 1988)
The use of international arbitration increased over the years as a result of growth in international trade. How the State intervenes in the process concerning the appointment of arbitrators, provisional measures and evidence, and in the enforcement of the judgment after arbitration, is analysed. This State practice is however, difficult to change since international arbitration operates in a structure based on differing national terms, and not on uniform international standards.